Influences of parental behaviors of solo fathers on adolescents' emotional attitudes and behaviors - Lalap, B. A. (Compendium of Human Ecology Researches in the Philippines, 2003)
This study was conducted to identify the influences of the paternal behaviors of temporary solo fathers on their adolescent children's emotional attitudes and behaviors. The respondents were adolescents aged 12 to 19 years old, residents of Nagcarlan, Laguna, whose fathers were ones taking care of them and their siblings while the mothers were working abroad. Findings showed that positive and negative parental characteristics and behaviors of the fathers have both positive and negative influences on adolescents emotional attitudes and behaviors. However, the negative effects were more manifested . Unkind or cruel paternal characteristics and behavior gave rise to negative impacts such as feeling worthless, unhappy, worried, anxious, and being secretive. A higher number of father-child anxious , and being secretive. A higher number of father-child respondents and a comparative study on gender differences in terms of emotional attitudes and behaviors can be considered in future research. Intensive and appropriately designed counseling and parenting/family seminars for left-behind fathers and adolescents are highly recommended to enhance positive father-child relationships.